Climate-Smart Agriculture: Leveraging Weekly Rainfall Trends for Rainfed Crops in West Bengal - Mukherjee, Joydeep; MANNA, TRISHA; BANERJEE, ABIRA (The Indian Journal of Agricultural Sciences, 2026)
Rainfall variability has a significant impact on rainfed agriculture, crop planning, and cropping patterns on a diverse agro-climatic zones. The present study employes incomplete gamma probability, initial and conditional probability and consecutive probability of weekly rainfall across Baharampur, Midnapore, Darjeeling, Sagar Island and Sriniketan. Baharampur recorded high probability of dry spell and limited sowing opportunities, while Midnapore recorded early and extended wet spell suitable for rainfed agriculture starting from Week 13. Darjeeling experiences concentrated monsoon from 22nd to 40th SMW and Sagar Island have wet spell from 23rd to 39th SMW followed by long dry spell. Sriniketan depicted a widespread monsoon week starting from 16th SMW to 43rd SMW. Conditional probability analysis was helpful for identifying the transition period from dry spell to wet spell and vice versa while consecutive probability analysis helped in identifying sustained rainfall or dry period.